PARADIGMA BIMBINGAN DAN KONSELING:PERGESERAN ORIENTASI DARI TERAPEUTIK-KLINIS KE PREVENTIF-PERKEMBANGAN - Sigit Sanyata (Paradigma, 2013)
Early development of counseling and psychotherapy is influenced by psychodynamic, respectively influences cognitive / behavioristik, and humanistic perspectives into the paradigm system of guidance and counseling. Paradigm shift aimed at the effectiveness of guidance and counseling not provide justification that the earlier theories are not well. Another important thing that must be understood by the counselor are all theories of counseling and psychotherapy have contributed in accordance with the concept and view of man with the attributes of the Problem. Shift towards preventive-seen significant growth for the period in which the learners should be given an equal opportunity to thrive.